Gulungan Laut Mati: Fakta Salinan yang Akurat - Hondro, Sipikir (Jurnal Salvation, 2025)
Abstract: The Dead Sea Scrolls show evidence that the copies of the Old Testament made by Jewish scribes are almost identical to the “Masoretic Text.” In explaining this, this paper will present an analysis of the Dead Sea Scrolls from a geographical, archaeological, and socio-cultural perspective. Copies of the text cannot be called infallible or inspired by the Holy Spirit, but the Dead Sea Scrolls are infallible and inspired by the Holy Spirit. The discovery of the Dead Sea Scrolls provides very important information about the accuracy of the Bible, especially the Old Testament. Literature analysis was also conducted to reveal the durability of the writing medium used in ancient times, known as papyrus, until eventually using leather shaped into scrolls. Abstrak: Naskah Gulungan Laut Mati menunjukkan bukti bahwa para penyalin Kitab Suci Perjanjian Lama yang dilakukan oleh para jurutulis Yahudi hampir tidak ada perbedaannya dengan “Teks Masoret”. Dalam menjelaskan hal ini, maka tulisan ini akan memaparkan analisis terhadap penemuan Naskah Gulungan Laut Mati dari Aspek Geografis, Arkeologi dan Sosial-budaya. Salinan-salinan teks tidak bisa disebut inaransi atau ilham Roh Kudus, tetapi Naskah Gulungan Laut Mati adalah inaransi dan ilham dari Roh Kudus. Temuan naskah Gulungan Laut Mati memberikan informasi yang sangat penting tentang keakuratan naskah Alkitab khusunya kitab Perjanjian lama. Analisis Pustaka juga dilakukan untuk mengungkapkan tentang ketahanan dari media tempat menulis pada zaman dahulu yang disebut tumbuhan papirus sampai akhirnya menggunakan kulit yang dibentuk benjadi gulungan-gulungan